La fiesta del Chivo: between power, law, fear and complicity - Morin Flores, Alba Nidia (2021)
This paper seeks to identify the conception of power in La fiesta del Chivo. The phenomenon of power from the literary subgenres of the region, its particularities and its problems are analyzed in this essay. After a process of interpretation and contextualization of the work, it is identified that the fundamental elements of the primary conception of power are violence, conflict, and fear. Despite the author’s little problematization of this topic, fear of the loss of the «order» imposed by the dictatorial figures highlights the relationship of complicity between the dictator, those close to him, and the governed. With this approach, the study reveals the complexity of the phenomena of power in the region and allows an approach to law as an instrument of legitimization of dictatorships.